The future of antivirals: broad-spectrum inhibitors. Issue 6 (December 2015) - Debing, Yannick; Neyts, Johan; Delang, Leen
Abstract : Purpose of review: Potent antivirals are successfully used for the treatment of infections with herpesviruses, hepatitis B and C viruses, HIV, and with some success for influenza viruses. However, no selective inhibitors are available for a multitude of medically important viruses, most of which are (re-)emerging RNA viruses. As it is impossible to develop drugs against each of these viruses, broad-spectrum antiviral agents (BSAA) are a prime strategy to cope with this challenge. Recent findings: We propose four categories of antiviral molecules that hold promise as BSAA. Several nucleoside analogues with broad antiviral activity have been described and given the relatively conserved nature of viral polymerases, it may be possible to develop more broad-spectrum nucleoside analogues. A number of viral proteins are relatively conserved between families and may also be interesting targets. Host-targeting antiviral drugs such as modulators of lipid metabolism and cyclophilin inhibitors can be explored as well. Finally, the potent and broad antiviral function of the immune system can be exploited by the development of immune-modulating BSAA. Summary: Despite the recent advances, the BSAA field is still in its infancy. Nevertheless, the discovery and development of such molecules will be a key aim of antiviral research in the coming decades.